2016
DOI: 10.1111/ajt.13690
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Induced Airway Epithelial Injury Drives Fibroblast Activation: A Mechanism in Chronic Lung Allograft Dysfunction

Abstract: Bacterial infections after lung transplantation cause airway epithelial injury and are associated with an increased risk of developing bronchiolitis obliterans syndrome. The damaged epithelium is a source of alarmins that activate the innate immune system, yet their ability to activate fibroblasts in the development of bronchiolitis obliterans syndrome has not been evaluated. Two epithelial alarmins were measured longitudinally in bronchoalveolar lavages from lung transplant recipients who developed bronchioli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 51 publications
3
42
0
Order By: Relevance
“…Our data indicate that this relationship is unique to Pseudomonas aeruginosa , as we did not detect an association between other bacteria, fungi, or viruses and DSA in our cohort. Several reports have demonstrated that Pseudomonas aeruginosa stimulates potent innate immune responses, including airway neutrophilia . Our group has also shown that Pseudomonas aeruginosa infection in a mouse model of lung transplantation promotes neutrophilia through a granulocyte‐colony stimulating factor‐dependent mechanism that prevents established tolerance .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our data indicate that this relationship is unique to Pseudomonas aeruginosa , as we did not detect an association between other bacteria, fungi, or viruses and DSA in our cohort. Several reports have demonstrated that Pseudomonas aeruginosa stimulates potent innate immune responses, including airway neutrophilia . Our group has also shown that Pseudomonas aeruginosa infection in a mouse model of lung transplantation promotes neutrophilia through a granulocyte‐colony stimulating factor‐dependent mechanism that prevents established tolerance .…”
Section: Discussionmentioning
confidence: 80%
“…18,22,37,38 Over half of those who had Pseudomonas aeruginosa isolation after transplantation were culture negative for Pseudomonas aeruginosa before transplantation. Moreover, the association between [39][40][41] Our group has also shown that Pseudomonas aeruginosa infection in a mouse model of lung transplantation promotes neutrophilia through a granulocyte-colony stimulating factor-dependent mechanism that prevents established tolerance. 39 Notably, we also observed that Pseudomonas aeruginosa infection induced allograft-infiltrating neutrophils to upregulate the B7 molecules CD80 and CD86, which in turn could drive alloantigen-specific T cell responses through providing B7:CD28 costimulation in trans.…”
Section: Pseudomonas Aeruginosa Our Multivariable Analysis Also Idenmentioning
confidence: 99%
“…Fibroblast activation can be driven by products of P. aeruginosa -injured epithelial cells such as IL-1α, and may underlie the development of BOS in lung transplant patients infected with P. aeruginosa . These individuals show increased levels of IL-1α, elevated IL-8 levels, and higher neutrophil percentages in bronchoalveolar lavage (BAL) fluid collected shortly before the diagnosis of BOS, as compared to post-transplant patients without BOS, and inflammation is temporally correlated with P. aeruginosa growth in BAL [56]. …”
Section: Immune Recognition and Response To P Aeruginosa Infectionmentioning
confidence: 99%
“…While in vitro models of OB have utility in showing how individual populations, such as bronchial epithelial cells, mesenchymal stromal cells, and airway smooth muscle cells, may contribute to disease (95)(96)(97)(98), animal models can provide a window into the events from transplant to the final fibrotic obliteration of small airways and is key to investigating the pathogenesis of OB and conducting preclinical studies of potential therapeutic interventions. Utilized models of post-lung-transplant OB are based on allogeneic lung tissue transplantation with a goal of reproducing fibrotic airway remodeling.…”
Section: Cladmentioning
confidence: 99%